Mandailing smoked fish cuisine: cultural, nutritional, and local wisdom insights - Esi Emilia; Nila Reswari Haryana; Risti Rosmiati; Erli Mutiara; Laili Fitria; Rachmat Mulyana; Wisnu Prayogo (Institute of Advanced Engineering and Science, 2025)
This study explores the uniqueness of Mandailing traditional cuisine, focusing on the cultural and nutritional significance of its iconic smoked fish dishes, such as smoked fish rendang, smoked fish curry, smoked fish with chili sauce, and smoked fish with vegetables. These dishes showcase the traditional fish smoking practices developed as a preservation method, allowing the Mandailing community to adapt to the abundance of rivers and natural resources in their highland environment. Smoking fish not only extended its shelf life but also became a cornerstone of Mandailing culinary identity, reflecting the community’s ingenuity and resourcefulness. Mandailing cuisine is deeply influenced by neighboring culinary traditions from West Sumatra and North Tapanuli, resulting in a rich fusion of bold flavors, often characterized using coconut milk and fresh spices. The preparation of smoked fish combines traditional high-heat cooking techniques with unique flavor profiles that distinguish Mandailing dishes from other Indonesian cuisines. This research highlights the importance of Mandailing smoked fish practices in sustaining local food systems and preserving cultural heritage. By emphasizing both cultural and nutritional aspects, it underlines the relevance of these traditional practices in promoting food diversity, environmental sustainability, and the recognition of Indonesia’s rich culinary landscape.